955Risk of drowning: the Japan Collaborative Cohort (JACC) Study. (2nd September 2021) - Kimura, Takashi; Ikehara, Satoyo; Tamakoshi, Akiko
Abstract: Background: In Japan, the unintentional drowning mortality rate among the elderly is exceptionally high. However, the risk factors for drowning in Japan are not fully understood. This study aims to explore the risk factors of drowning in Japan. Methods: This study used data from the Japan Collaborative Cohort Study, a prospective cohort aged 40–79 years initiated 1988-1990. A total of 86, 298 individuals (35, 984 men and 50, 314 women) completed a self-administered questionnaire and were mainly followed up by the end of 2009. We calculated hazard ratios (HRs) and 95% confidence intervals (95%CIs) for drowning according to age, body mass index, drinking habits, medical history, marital status, and years of education. Results: A total of 194 drownings occurred during a median follow-up period of 18.9 years. The multivariable HRs (95%CIs) of drowning were 0.21 (0.10–0.45) for aged <50 years, 0.37 (0.21-0.65) for 50–59 years compared with 60–69 years, 3.08 (1.39–6.85) for bereaved compared with married, 3.39 (1.19-9.66) for with medical history of stroke compared without, and 3.18 (1.39–7.30) for current drinker with ≥69.0g ethanol/day compared with never drinker in men,  0.20 (0.09-0.43) for aged <50 years and 3.39 (1.19-9.66) for 50-59 years in women. Conclusions: Younger people were found to have a lower risk of drowning. For men, bereavement, history of stroke, and current heavy drinking were found to have higher risk of drowning. Key messages: In Japan, bereavement, a history of stroke, and heavy drinking among men found to have higher risk of drowning